Exposure of midwives to nitrous oxide in four hospitals. Issue 6554 (25th October 1986) - Munley, A J; Railton, R; Gray, W M; Carter, K B
Abstract : The exposure of midwives to nitrous oxide in four hospitals was measured with personal samplers. In three of the four hospitals the average exposure was not significantly less than 100 parts per million (ppm). In one hospital the average exposure was 360 ppm; this was reduced by a factor of about 2.5 when a trial scavenging system was used. Differences in working practices and in the layout, size, and ventilation of the labour suites contributed to the observed differences in average exposure. Midwives and other staff working in the labour room are potentially at risk from excessive occupational exposure to nitrous oxide.